Social protection expansions during crisis and fiscal space: From ad hoc to durable solutions? - Annalena Oppel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This study provides a first attempt to contribute a large-scale assessment of whether crisis response as observed during the COVID-19 pandemic can serve as a feasible blueprint for creating durable solutions across countries. Adopting a lens on fiscal contracts, it assesses highlevel parameters of both the collection and the spending sides of public finance. More precisely, it contrasts fiscal and political feasibility by considering fiscal capacity, policy portfolios, and existing inequality levels. To do so, it draws on UNU-WIDER's Government Revenue Dataset, containing measures on total non-tax and tax revenue as well as subcomponents. It further combines this dataset with the COVID-19 Stimulus Tracker of the United Nations Economic and Social Commission for Western Asia, comprising more than 7,000 policy measures implemented as a response to the challenges brought forth by the pandemic. Using an unsupervised clustering algorithm (k-means), it groups countries according to three key metrics: fiscal excess, spending diversity, and inequality as measured by the Gini coefficient. The study highlights countries' unequal capacity to respond to covariate shocks such as the pandemic, in both fiscal and political terms. While it has been argued that the pandemic accelerated a declining trend in between-country inequality, these vastly unequal crisis response abilities may reverse this trend in the long term. In addition, current social protection policy expansions and perhaps innovations seem to be more fiscally and politically feasible for high-income countries that are also characterized by greater equality in resource distribution and comparatively higher public goods spending. Overall, country group differences may limit the role of crisis response during COVID-19 as potential blueprints in crafting adaptive, inclusive, and sustainable systems in less-developed economies.
Keywords: C38; H5; H84; I00; 330; fiscal contracts; crisis response; social protection; tax revenue; k-means clustering; pandemic